Piercing the Corporate Veil: Searching for Appropriate Choice of Law Rules - THAM, Chee Ho (Institutional Knowledge at Singapore Management University, 2007)
The question when an English court will lift the corporate veil is by no means easy to answer, even when the facts are wholly domestic. Obviously, the question will be rendered even more complex if the company against which an application involving veil-lifting is sought is not an English company—the immediate question one faces is, which law should govern this question: the lex incorporationis or some other law? On the analysis undertaken in this paper, the answer is: “It depends.” Starting from the recognition that corporate veil-lifting is not a singular concept, this paper argues that no single choice of law rule can therefore govern. Instead, a more nuanced, but fragmented, approach to characterization of the true issues is proposed.